Рушники в зібранні шевченківського національного заповідник - Брижицька, С. (Народна творчість та етнографія, 2007)
The article is about practical approaches to the forming of exposition of rushnyky (Ukrainian embroidered towels) in Shevchenko National Park in Kaniv. Collecting rushnyky was based on regional principle. The author focused on rushnyky which were made or existed in Naddnipryanska Ukraine (Left-bank Ukraine) – the homeland of Taras Shevchenko. Embroidered and woven rushnyky and the photos of them are presented in the article.